Production system shell for mobile Devices - Shapovalova, S.I.; Mazhara, O.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2015)
The CLIPS shell extension was proposed to enable the creation of applied production systems which can be used on mobile devices. The innovation was substantiated in terms of saving money resources to purchase specialized equipment for using for the resource-intensive production systems. The following studies were conducted: market research tablet devices, the most widely represented in Ukraine; production systems shells that can be used on mobile devices; freely distributable production systems shells were considered, important characteristics were identified and compared. The basic classes of match algorithms were overviewed. The results of studies about Rete and Treat match algorithms advisability were described for the general case of the applied problems. The proposed modeling environment for production systems for mobile devices will reduce development time and increase system efficiency by choosing the optimal match algorithm for minimal memory usage.